1999
DOI: 10.1111/j.1502-3885.1999.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary environmental history of central Prins Karls Forland, western Svalbard

Abstract: This paper presents the results from stratigraphic and geomorphologic investigations in the Poolepynten area, Prins Karls Forland, western Svalbard. Field mapping, soil profile development and 14 C dating reveal the existence of at least two generations of raised beach deposits. Well-developed raised beaches rise to the Late Weichselian marine limit at 36 m a.s.l. Discontinuous pre-Late Weichselian beach deposits rise from the Late Weichselian marine limit to approximately 65 m a.s.l. Expansion of local glacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
84
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(94 citation statements)
references
References 49 publications
10
84
0
Order By: Relevance
“…[2]) from an extended valley glacier, or possibly a tributary to a fjord glacier. This local ice-flow signature is similar to what has been noted for other sites on Svalbard, particularly on the west coast [10,63,[69][70][71][72] and has been assumed to reflect a predominantly low-activity, possibly even frozen-bed ice-sheet cover over these inter-fjord areas [2].…”
Section: Subglacial: Scarce Direct Traces Of Ice Coversupporting
confidence: 61%
See 1 more Smart Citation
“…[2]) from an extended valley glacier, or possibly a tributary to a fjord glacier. This local ice-flow signature is similar to what has been noted for other sites on Svalbard, particularly on the west coast [10,63,[69][70][71][72] and has been assumed to reflect a predominantly low-activity, possibly even frozen-bed ice-sheet cover over these inter-fjord areas [2].…”
Section: Subglacial: Scarce Direct Traces Of Ice Coversupporting
confidence: 61%
“…Similar observations have been made in marine or littoral units at, e.g. Leinstranda [10] and Poolepynten [14,69] and a fairly extensive dating program with laterally and vertically distributed samples must be recommended when working with this type of sediments and questions.…”
Section: Marine and Littoral: Vital Chronological Keys And Glacial Inmentioning
confidence: 96%
“…Thus, our results clearly demonstrate that the jaw is from an individual that had a feeding ecology similar to presentday polar bears, at the top of the Arctic marine food chain. Furthermore, analyses of the stratum containing the subfossil jawbone uncovered a bivalve and foraminifera fauna reflecting an arctic, open marine environment influenced by glacier input and advection of warm North Atlantic water as today (11,14).…”
Section: Resultsmentioning
confidence: 99%
“…Diagnostic polar bear traits and morphometric measurements of this well-preserved mandible, comparing it to brown bear and other available subfossil polar bear remains as well as a large collection of extant polar bears from Svalbard, proved that it falls within the range of modern polar bears and suggested that it belonged to an adult male (11). Accelerator mass spectrometry 14 C age determination from a canine tooth attached to the jawbone dated it to older than 45 thousand years (ky) old (11). Based on long-term studies of the stratigraphy and depositional history of the Poolepynten area and infrared-stimulated luminescence of the sediments (14), the specimen was estimated to be 130-110 ky old, which is significantly older than any other known polar bear subfossils (i.e., To whom correspondence should be addressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation